Genome-wide characterization of cys-tathionine-β-synthase domain-containing proteins in sugarcane reveals their role in defense responses under multiple stressors - Zhou, Jing-Ru; Li, Juan; Lin, Jia-Xin; Xu, Hui-Mei; Chu, Na; Wang, Qin-Nan; Gao, San-Ji (Frontiers in Plant Science, 2022)
The cys-tathionine-β-synthase (CBS) domain containing proteins (CDCPs) are essential players in regulating plants responses to various biotic and abiotic stressors. This study systematically marked the identification and characterization of CDCP family genes in Saccharum spontaneum. A total of 95 SsCDCP genes and eight phylogenetic groups were identified, distributing on 29 chromosomes of AP85-441 genome. Majority of SsCDCPs (77/95) underwent fragment duplication events and 64 gene pairs of them located in synteny blocks. Furthermore, expression profiling of nine ShCDCPs were carried out in two Saccharum spp. cultivars ROC22 (resistant to red stripe) and MT11-611 (susceptible to red stripe) in response to bacterial pathogen Acidovorax avenue subsp. avenae (Aaa) infection and abiotic stressors (drought and salinity) as well as exogenous salicylic acid (SA) treatment. One gene pair (ShCBSD-PB1-5A vs. ShCBSD-PB1-7A-1) with fragment duplication event severed as negative regulators in sugarcane under four stresses, suggesting they shared function redundance. Another gene pair (ShCBS-4C vs. ShCBS-4D-1) with fragment duplication event play opposite regulatory roles in sugarcane under multiple stress, particularly Aaa and NaCl treatments, suggesting both genes exhibited function divergence. In addition, the gene SsCBSDCBS-5A was significantly upregulated in ROC22 stimulated by the four stressors. These findings provide important clues for further elucidating these ShCDCPs gene functions in sugarcane against diverse stresses.